2023
DOI: 10.3390/su15076112
|View full text |Cite
|
Sign up to set email alerts
|

Sewage Sludge Management and Application in the Form of Sustainable Fertilizer

Abstract: One of the most pressing environmental problems worldwide is sewage sludge (SS) management. Every year, wastewater volume increases and thus, the amount of SS produced increases as well. The disposal of SS in landfills, as practiced in many countries, is not a sustainable solution. Instead, SS, rich in organic matter and other nutrients, can be used as an alternative soil additive or fertilizer. The properties of these materials depend on their chemical composition and the method of treatment. Experience from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 74 publications
0
2
0
2
Order By: Relevance
“…Anaerobic digestion, for instance, allows for the conversion of organic matter in SS into biogas, cost effective, minimizing greenhouse gas emissions and reducing the potential for global warming ( Rorat et al., 2019 ; Teoh and Li, 2020 ). Additionally, composting or co-composting with other biodegradable wastes and additives is an important treatment method for SS, enabling a significant reduction in volume and minimal emissions of hazardous substances, making it environmentally acceptable when compared to incineration ( Sugurbekova et al., 2023 ). It has been also observed that applying sewage sludge at lower doses presents minimal risks to the environment, while simultaneously enhancing the grain yield and quality of crops.…”
Section: The Feasibility Environmental Risk and Mitigation Strategies...mentioning
confidence: 99%
“…Anaerobic digestion, for instance, allows for the conversion of organic matter in SS into biogas, cost effective, minimizing greenhouse gas emissions and reducing the potential for global warming ( Rorat et al., 2019 ; Teoh and Li, 2020 ). Additionally, composting or co-composting with other biodegradable wastes and additives is an important treatment method for SS, enabling a significant reduction in volume and minimal emissions of hazardous substances, making it environmentally acceptable when compared to incineration ( Sugurbekova et al., 2023 ). It has been also observed that applying sewage sludge at lower doses presents minimal risks to the environment, while simultaneously enhancing the grain yield and quality of crops.…”
Section: The Feasibility Environmental Risk and Mitigation Strategies...mentioning
confidence: 99%
“…2) рідкої фракції із вмістом сухих речовин 1-8%, збагаченої азотом та калієм. На практиці існують два основних напрямки обробки дигестату з метою подальшого використання його як добрива, можливості подальшого транспортування отриманого продукту, виокремлення окремих складових, які можуть бути цінними для підвищення родючості ґрунтів [5,6].…”
Section: аналіз останніх досліджень і публікаційunclassified
“…Several physical, chemical and biological processes have been developed to minimize sludge production [35][36][37]. The most common methods for disposing sewage sludge are incineration, landfilling [38,39] or reuse in agriculture [40,41]. Recently, new technologies have been developed for their utilization, with particular attention paid to the lipid component, which can produce biodiesel.…”
Section: Introductionmentioning
confidence: 99%